Why crystal gaze... you can start closing loops now with a Beckman 112 Data Processing System - Beckman Instruments, Inc.; Charles Bowes Advertising (1960)
Beckman Instruments' analog computers were developed by their Berkeley Division as early as 1953. The company produced analog computers -- also called automation, data reduction, or data handling systems -- for the petroleum, aerospace, and defense industries. Beckman Instruments eventually stopped producing these systems after their cost and the time required to customize them kept them from being widely adopted.
Keywords: Electronic data processing; Computer industry--United States--History; Crystal gazing; Computers--History; Beckman Instruments, Inc.